Outcomes of Nonvigorous Neonates Born through Meconium-Stained Amniotic Fluid after a Practice Change to No Routine Endotracheal Suctioning from a Developing Country - Kumar, Gunjana; Goel, Srishti; Nangia, Sushma; Ramaswamy, Viraraghavan Vadakkencherry (American Journal of Perinatology, 2022)
Objective The International Liaison Committee on Resuscitation (ILCOR) 2015 gave a weak recommendation based on low certainty of evidence against routine endotracheal (ET) suctioning in non-vigorous (NV) neonates born through meconium-stained amniotic fluid (MSAF) and suggested for immediate resuscitation without direct laryngoscopy. A need for ongoing surveillance post policy change has been stressed upon. This study compared the outcomes of NV MSAF neonates before and after implementation of the ILCOR 2015 recommendation.Study Design This was a prospective cohort study of term NV MSAF neonates who underwent immediate resuscitation without ET suctioning (no ET group, July 2018 to June 2019, n = 276) compared with historical control who underwent routine ET suction (ET group, July 2015 to June 2016, n = 271).Results Baseline characteristics revealed statistically significant higher proportion of male gender and small for gestational age neonates in the prospective cohort. There was no significant difference in the incidence of primary outcome of meconium aspiration syndrome (MAS) between the groups (no ET group: 27.2% vs ET group: 25.1%; p = 0.57). NV MSAF neonates with hypoxic ischemic encephalopathy (HIE) was significantly lesser in the prospective cohort (no ET group: 19.2% vs ET group: 27.3%; p = 0.03). Incidence of air leaks and need for any respiratory support significantly increased after policy change. In NV MSAF neonates with MAS, need for mechanical ventilation (MV) (no ET group: 24% vs ET group: 39.7%; p = 0.04) and mortality (no ET group: 18.7% vs ET group: 33.8%; p = 0.04) were significantly lesser.Conclusion Current study from a developing country indicates that immediate resuscitation and no routine ET suctioning of NV MSAF may not be associated with increased risk of MAS and may be associated with decreased risk of HIE. Increased requirement of any respiratory support and air leak post policy change needs further deliberation. Decreased risk of MV and mortality among those with MAS was observed.Key Points
Keywords: meconium aspiration syndrome; nonvigorous neonate; delivery room resuscitation; endotracheal suction; meconium-stained amniotic fluid